Spectral and dynamic confocal fluorescence characterization of cytogenetic preparations - Kahn, Edmond; Hotmar, Jan; Frouin, Frédérique; Di Paola, Mireille; Bazin, Jean-Pierre; Di Paola, Robert; Bernheim, Alain (Analytical cellular pathology, 1996)
Investigations were performed on fluorescent in situ hybridization (FISH) preparations to examine whether factor analysis of medical image sequences (FAMIS) can be used to isolate fluorescent probes by means of their spectral and/or extinction dynamic emission properties. FISH is used to track down chromosomes of interest in cell nuclei and mitoses. Cytogenetic techniques producing flat preparations of whole cells were assumed to preserve the probes' access to their targets. To isolate the result of hybridization in the human nuclear interphase, we used a confocal microscope. Labelling of the targets by the probes (sequences labelled by FITC and TRITC) in the nuclei stained by propidium iodide was used as a biological model. We used two methods to isolate the component parts of the model: multispectral analysis and dynamic studies. In the case of multispectral analysis, the investigation was performed on 2D and 3D sequences of 28 images obtained on a single photomultiplier (PM) detector of the confocal microscope by selection of emission through 10-nm interference filters in the range of 500-780 nm and by z-displacement in each filter setting. In the case of dynamic studies, the investigation was performed on sequences of 30-70 images obtained on the same detector by single or average integrated acquisition of 10-30 scans. Confocal scanning yields images with constant excitation time. These images were investigated by FAMIS and the results revealed that the spectra and kinetics as factors, and factor images corresponded to FITC and TRITC stained targets, as well as to propidium iodide stained interphase. In conclusion, we would verify that targets were isolated through the spectrum of the fluorescent probes and could be distinguished from the propidium iodide used to stain the nuclei. It was also possible to distinguish them from the propidium iodide by taking into account differences in photobleaching of the different fluorochromes. The study leads us to process displacements by registration methods prior to factor analysis to improve the results.
Keywords: fluorescein-5-isothiokyanát; Fluorescein-5-isothiocyanate; fluorescenční barviva; konfokální mikroskopie; Humans; Fluorescent Dyes; mužské pohlaví; Male; lidé; Lymphocytes; Microscopy, Confocal; lymfocyty; In Situ Hybridization; hybridizace in situ